Pengaruh Sikap Toleransi Beragama terhadap Kualitas Interaksi Sosial antarsiswa di SMK Pembangunan Ampel Boyolali - Sukiman Bagaskara; Kabri Kabri; Sukisno Sukisno (Universitas Hamzanwadi, 2026)
This study was motivated by the importance of strengthening students' attitudes toward religious tolerance in fostering the quality of social interaction within a multicultural school environment. The diversity of religious backgrounds in schools requires students to develop the ability to respect differences, cooperate with others, and establish harmonious social relationships. This study aimed to analyze the level of religious tolerance attitudes, the quality of students' social interaction, and the effect of religious tolerance attitudes on the quality of social interaction among students at SMK Pembangunan Ampel Boyolali. This study employed a survey method using a quantitative approach. The research participants were students of SMK Pembangunan Ampel Boyolali in the 2025/2026 academic year. A total of 125 students were selected using the proportional total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, prerequisite tests, and simple linear regression with SPSS. The findings revealed that religious tolerance attitudes had a positive and statistically significant effect on the quality of students' social interaction at SMK Pembangunan Ampel Boyolali. The coefficient of determination (R² = 0.620) indicated that religious tolerance attitudes accounted for 62.0% of the variance in students' social interaction quality, representing a high level of contribution. Furthermore, the correlation coefficient (r = 0.764) demonstrated a strong positive relationship between religious tolerance attitudes and students' social interaction quality. The regression analysis also showed statistical significance (Sig. = 0.00< 0.05), confirming that religious tolerance attitudes significantly influenced students' social interaction. Overall, the findings indicate that religious tolerance is an important factor in promoting positive and harmonious social relationships among students in a multicultural school environment.